2022
DOI: 10.7759/cureus.23837
|View full text |Cite
|
Sign up to set email alerts
|

Physician Satisfaction With Virtual Ophthalmology Clinics During the COVID-19 Pandemic: A Tertiary Eye Care Center Experience

Abstract: Background In this study, we aimed to assess ophthalmologists’ experience with teleophthalmology during the coronavirus disease 2019 (COVID-19) pandemic in the central region of Saudi Arabia. In addition, we evaluated their satisfaction level and explored their satisfaction determinants. Methodology We conducted an online survey for ophthalmologists who participated in the virtual ophthalmology clinic during COVID-19 between November 2020 and September 2021. The survey was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…In another study performed by Rhodes [14], 71% of patients agreed or were neutral to receiving telediagnosis and 74% of patients agreed or were neutral to receiving teleintervention. In a survey addressed to physicians by Adi M. Al Owaifeer et al [15], 56.3% of the respondents were satis ed with teleophthalmology, being the retina specialists who demonstrated higher levels of satisfaction than other subspecialties.…”
Section: Discussionmentioning
confidence: 99%
“…In another study performed by Rhodes [14], 71% of patients agreed or were neutral to receiving telediagnosis and 74% of patients agreed or were neutral to receiving teleintervention. In a survey addressed to physicians by Adi M. Al Owaifeer et al [15], 56.3% of the respondents were satis ed with teleophthalmology, being the retina specialists who demonstrated higher levels of satisfaction than other subspecialties.…”
Section: Discussionmentioning
confidence: 99%
“…Many centers adopted the virtual clinic concept to triage the patients, directing the urgent cases to the available channels. [ 27 28 ] They utilized a real-time video call with the patients to conduct the clinical appointments. While this helped filter out patients who did not need to be present physically, the major challenge was the inability to do microscopic clinical examinations, the findings of which ophthalmologists usually depend on to make their clinical decisions.…”
Section: T Elemedicine and T Eleophthalm...mentioning
confidence: 99%
“…conducted a study exploring physicians’ perceptions toward teleconsultation in a tertiary care hospital during the COVID-19 pandemic. [ 27 ] They found that 56.3% were satisfied. The main reasons for dissatisfaction were the lack of adequate equipment to evaluate the patients (53.5%), followed by technical issues (43.7%) and patients’ lack of experience in using virtual consultation services (38%).…”
Section: T Elemedicine and T Eleophthalm...mentioning
confidence: 99%
“…To tackle system overload, various multidisciplinary collaborations and service delivery innovations have been tested, including telemedicine and virtual clinics, which allow rapid and reliable patient assessment [2] through the efficient usage of consultant time by assuring complementary exams are being performed on schedule, and by organizing their information in a user-friendly platform to ensure rapid decision-making in compliance with up-to-date guidelines. [3] In ophthalmology, many virtual clinics have been established worldwide [4][5][6][7][8][9] to deal with the heavy burden of patient referral and follow-up appointment overload, particularly in glaucoma and retina departments. Kotecha et al [8,10,11] described the development process of a virtual clinic for glaucoma patient follow-up at Moorfields Eye Hospital in London, whereas Trikha et al [12] described using virtual clinics as a triage model for patient prioritization upon glaucoma referral.…”
Section: What Is Newmentioning
confidence: 99%